A study of the gut contents of compressed tubby (Canthigaster compresa) from Talibon, Bohol and Palompon, Leyte, Philippines. - Caduada, Laymart A.
The Philippines has one of the longest coastlines and is among the top producers of fisheries products in the world. The industry however is threatened by unsustainable fishing practices and dwindling resources. Proper fisheries management is hindered by an extensive lack of biological information on resource populations. Studying fish feeding habits based on gut content analysis could provide insights on fish feeding patterns and trophic interactions in aquatic food webs and enhance our understanding of exploited resources. The study compared the composition of the gut contents of Canthigaster compressa caught by sled trawl in seagrass beds in Talibon, Bohol and Palompon, Leyte. Sixty eight specimens from Talibon and 80 from Palompon were examined. Chyme made up 70-76% of the total gut contents in both areas. A total of 23 prey items were observed. Diet composition in Palompon was more diverse as compared to Talibon. Gut contents changed with size/age, with an apparent increase in the proportion of seagrass/algae as fish size increased. This suggests that the tubby shifts to a more herbivorous diet as they grow older. The amount of forams in the guts also decreased with size which could be attributed to a shift in habitat from seagrass to coral reefs. The results also show that crustaceans are more abundant n Palompon than in Talibon which could mean that Palompon has a richer seagrass-associated crustacean population. Further studies about the abundance of crustaceans in the fish diet in Palompon and Talibon is encouraged as it could be useful in assessing the ecological conditions of the areas.